The paramedic companion a case-based worktext - Hsieh, Arthur; Boone, Kevin (New York McGraw-Hill higher education, 2008)
Foundations of paramedicine; Foundations of communication, assessment, and critical care; Trauma; Medical issues; Special populations; Operations.
Includes bibliographical references and index
Keywords: Emergency medical services -- Case studies; Emergency medical technicians; Dịch vụ y tế